Flexible Solar Interfacial Evaporators with Photocatalytic Function for Purification of High-Salinity Organic Wastewater - Yucheng Li; Xia Zhao; Tao Hu; Lingxiao Li; Xiaopeng Huang; Junping Zhang (Nanomaterials)
Solar-driven interfacial water evaporation technology coupled with photocatalytic function is regarded as an emerging approach for treating high-salinity organic wastewater, but it remains challenging to design high-performance solar evaporators with excellent photocatalytic properties. Here, we designed a two-dimensional flexible solar interfacial evaporator with photocatalytic function for the purification of high-salinity organic wastewater. The solar evaporator was prepared by the deposition of Cu-based metal organic frameworks (Cu-MOFs) onto a polyester fabric by solvothermal reaction, during which graphitic carbon nitride was also deposited as carried by Cu-MOFs. The solar evaporator achieves an outstanding evaporation rate of 1.95 kg m−2 h−1 for simulated seawater (3.5 wt% NaCl) under 1 sun. The evaporator also shows efficient evaporation performance and salt resistance for high-concentration saline water due to its outstanding water transport capacity and efficient light absorption ability. Furthermore, salt ions and organic pollutants can be simultaneously removed from high-salinity organic wastewater by the evaporator due to the synergistic effects of adsorption, the photothermal effect and photocatalytic performance. This study successfully integrated photocatalytic technology with solar-driven interfacial evaporation, extending the multifunctionality of solar evaporators for treating high-salinity organic wastewater.